Solution of trigonometric equation avoiding the undefined case
![Creative The name of the picture](https://blogger.googleusercontent.com/img/b/R29vZ2xl/AVvXsEgO9GURib1T8z7lCwjOGLQaGtrueEthgQ8LO42ZX8cOfTqDK4jvDDpKkLFwf2J49kYCMNW7d4ABih_XCb_2UXdq5fPJDkoyg7-8g_YfRUot-XnaXkNYycsNp7lA5_TW9td0FFpLQ2APzKcZ/s1600/1.jpg)
![Creative The name of the picture](https://blogger.googleusercontent.com/img/b/R29vZ2xl/AVvXsEhYQ0N5W1qAOxLP7t7iOM6O6AzbZnkXUy16s7P_CWfOb5UbTQY_aDsc727chyphenhyphen5W4IppVNernMMQeaUFTB_rFzAd95_CDt-tnwN-nBx6JyUp2duGjPaL5-VgNO41AVsA_vu30EJcipdDG409/s400/Clash+Royale+CLAN+TAG%2523URR8PPP.png)
up vote
3
down vote
favorite
I'm given this trigonometric equation,
$$tan x+tan 2x=1-tan xtan 2x$$
I rewrote it as $$dfractan x+tan 2x1-tan xcdottan 2x=1$$
Using the identity, $$tan (A+B)=dfractan A+tan B1-tan Acdottan B$$ I simplified my equation as $$tan (x+2x)=1$$ which implies $$3x=dfracpi4+npi$$
So, $$x=dfracpi12+ncdotdfracpi3$$
Where, $n$ is an integer.
However, when $n=5$, $tan (2x)$ is undefined.
This is causing a problem.
WolframAlpha gave solutions which avoids my case.
How do I come to the solution which WolframAlpha gives?
trigonometry wolfram-alpha
add a comment |Â
up vote
3
down vote
favorite
I'm given this trigonometric equation,
$$tan x+tan 2x=1-tan xtan 2x$$
I rewrote it as $$dfractan x+tan 2x1-tan xcdottan 2x=1$$
Using the identity, $$tan (A+B)=dfractan A+tan B1-tan Acdottan B$$ I simplified my equation as $$tan (x+2x)=1$$ which implies $$3x=dfracpi4+npi$$
So, $$x=dfracpi12+ncdotdfracpi3$$
Where, $n$ is an integer.
However, when $n=5$, $tan (2x)$ is undefined.
This is causing a problem.
WolframAlpha gave solutions which avoids my case.
How do I come to the solution which WolframAlpha gives?
trigonometry wolfram-alpha
add a comment |Â
up vote
3
down vote
favorite
up vote
3
down vote
favorite
I'm given this trigonometric equation,
$$tan x+tan 2x=1-tan xtan 2x$$
I rewrote it as $$dfractan x+tan 2x1-tan xcdottan 2x=1$$
Using the identity, $$tan (A+B)=dfractan A+tan B1-tan Acdottan B$$ I simplified my equation as $$tan (x+2x)=1$$ which implies $$3x=dfracpi4+npi$$
So, $$x=dfracpi12+ncdotdfracpi3$$
Where, $n$ is an integer.
However, when $n=5$, $tan (2x)$ is undefined.
This is causing a problem.
WolframAlpha gave solutions which avoids my case.
How do I come to the solution which WolframAlpha gives?
trigonometry wolfram-alpha
I'm given this trigonometric equation,
$$tan x+tan 2x=1-tan xtan 2x$$
I rewrote it as $$dfractan x+tan 2x1-tan xcdottan 2x=1$$
Using the identity, $$tan (A+B)=dfractan A+tan B1-tan Acdottan B$$ I simplified my equation as $$tan (x+2x)=1$$ which implies $$3x=dfracpi4+npi$$
So, $$x=dfracpi12+ncdotdfracpi3$$
Where, $n$ is an integer.
However, when $n=5$, $tan (2x)$ is undefined.
This is causing a problem.
WolframAlpha gave solutions which avoids my case.
How do I come to the solution which WolframAlpha gives?
trigonometry wolfram-alpha
edited Aug 7 at 15:06
asked Aug 7 at 15:02
user571036
27818
27818
add a comment |Â
add a comment |Â
4 Answers
4
active
oldest
votes
up vote
2
down vote
Note that the statement $$dfractan x+tan 2x1-tan xcdottan 2x=1$$ is valid only if the denominator $$1-tan xcdottan 2x ne 0$$
We need to exclude the values for which $$ tan xcdottan 2x=1$$ from the solutions that you have found.
This latest equation is not hard to solve and I let you handle it.
add a comment |Â
up vote
0
down vote
i would use that $$tan(2x)=frac2tan(x)1-tan^2(x)$$
Then you will get
$$tan(x)+frac2tan(x)1-tan^2(x)=1-frac2tan^2(x)1-tan^2(x)$$
now substitute $tan(x)=t$
Substituting $tan x=t$ we get $t^3-3t^2-3t+1=0$ which is much more harder to work with.
â user571036
Aug 7 at 15:25
Not at all, it is $t^3-3t^2-3t+1=(t+1)(t^2-4t+1)$
â Dr. Sonnhard Graubner
Aug 7 at 15:30
Then give me the full solution.
â user571036
Aug 7 at 15:35
I would say please, but you will get $tan(x)=-1$ or $tan(x)=2pm sqrt3$
â Dr. Sonnhard Graubner
Aug 7 at 15:38
add a comment |Â
up vote
0
down vote
You can divide with $tan x tan 2x-1$ iff $tan x tan 2xne 1$
so $$2tan^2xover 1-tan^2x neq 1implies tan x neq pmsqrt3over 3 $$
so $xneq pm pi over 6+pi cdot k;; k in mathbbZ$.
add a comment |Â
up vote
0
down vote
The particular solutions ($0<x<2 pi$) are $dfrac pi 12$ and $dfrac 5 pi 12$, but when you work out both Wolfram Alpha's and the OP's solution, both general solutions come out to $$dfrac pi (4n+1)12$$
The problem with that is you have to have a restriction for $n=2, n=5, n=8$ and $n=11$, which causes $tan 2x$ to be undefined. To restrict those values, we can write
$$begincases
x = infty, & text$forall n$ a multiple of $3n-1$ \
x = dfrac pi (4n+1)12, & text$forall n$ not a multiple of $3n-1$
endcases$$
The reason why Wolfram Alpha wrote its general solutions as $$x = n pi - dfrac 7 pi12 text and x = n pi - dfrac 11 pi12$$ are because the negative angles are complementary to the positive ones, i.e. $frac pi 12$ and $frac 5 pi 12$ counterclockwise around the unit circle are equivalent to $-frac 7 pi 12$ and $-frac 11 pi 12$ clockwise around the unit circle. They also avoid the the undefined solutions altogether.
add a comment |Â
4 Answers
4
active
oldest
votes
4 Answers
4
active
oldest
votes
active
oldest
votes
active
oldest
votes
up vote
2
down vote
Note that the statement $$dfractan x+tan 2x1-tan xcdottan 2x=1$$ is valid only if the denominator $$1-tan xcdottan 2x ne 0$$
We need to exclude the values for which $$ tan xcdottan 2x=1$$ from the solutions that you have found.
This latest equation is not hard to solve and I let you handle it.
add a comment |Â
up vote
2
down vote
Note that the statement $$dfractan x+tan 2x1-tan xcdottan 2x=1$$ is valid only if the denominator $$1-tan xcdottan 2x ne 0$$
We need to exclude the values for which $$ tan xcdottan 2x=1$$ from the solutions that you have found.
This latest equation is not hard to solve and I let you handle it.
add a comment |Â
up vote
2
down vote
up vote
2
down vote
Note that the statement $$dfractan x+tan 2x1-tan xcdottan 2x=1$$ is valid only if the denominator $$1-tan xcdottan 2x ne 0$$
We need to exclude the values for which $$ tan xcdottan 2x=1$$ from the solutions that you have found.
This latest equation is not hard to solve and I let you handle it.
Note that the statement $$dfractan x+tan 2x1-tan xcdottan 2x=1$$ is valid only if the denominator $$1-tan xcdottan 2x ne 0$$
We need to exclude the values for which $$ tan xcdottan 2x=1$$ from the solutions that you have found.
This latest equation is not hard to solve and I let you handle it.
answered Aug 7 at 15:38
![](https://i.stack.imgur.com/7TAC1.jpg?s=32&g=1)
![](https://i.stack.imgur.com/7TAC1.jpg?s=32&g=1)
Mohammad Riazi-Kermani
27.9k41852
27.9k41852
add a comment |Â
add a comment |Â
up vote
0
down vote
i would use that $$tan(2x)=frac2tan(x)1-tan^2(x)$$
Then you will get
$$tan(x)+frac2tan(x)1-tan^2(x)=1-frac2tan^2(x)1-tan^2(x)$$
now substitute $tan(x)=t$
Substituting $tan x=t$ we get $t^3-3t^2-3t+1=0$ which is much more harder to work with.
â user571036
Aug 7 at 15:25
Not at all, it is $t^3-3t^2-3t+1=(t+1)(t^2-4t+1)$
â Dr. Sonnhard Graubner
Aug 7 at 15:30
Then give me the full solution.
â user571036
Aug 7 at 15:35
I would say please, but you will get $tan(x)=-1$ or $tan(x)=2pm sqrt3$
â Dr. Sonnhard Graubner
Aug 7 at 15:38
add a comment |Â
up vote
0
down vote
i would use that $$tan(2x)=frac2tan(x)1-tan^2(x)$$
Then you will get
$$tan(x)+frac2tan(x)1-tan^2(x)=1-frac2tan^2(x)1-tan^2(x)$$
now substitute $tan(x)=t$
Substituting $tan x=t$ we get $t^3-3t^2-3t+1=0$ which is much more harder to work with.
â user571036
Aug 7 at 15:25
Not at all, it is $t^3-3t^2-3t+1=(t+1)(t^2-4t+1)$
â Dr. Sonnhard Graubner
Aug 7 at 15:30
Then give me the full solution.
â user571036
Aug 7 at 15:35
I would say please, but you will get $tan(x)=-1$ or $tan(x)=2pm sqrt3$
â Dr. Sonnhard Graubner
Aug 7 at 15:38
add a comment |Â
up vote
0
down vote
up vote
0
down vote
i would use that $$tan(2x)=frac2tan(x)1-tan^2(x)$$
Then you will get
$$tan(x)+frac2tan(x)1-tan^2(x)=1-frac2tan^2(x)1-tan^2(x)$$
now substitute $tan(x)=t$
i would use that $$tan(2x)=frac2tan(x)1-tan^2(x)$$
Then you will get
$$tan(x)+frac2tan(x)1-tan^2(x)=1-frac2tan^2(x)1-tan^2(x)$$
now substitute $tan(x)=t$
answered Aug 7 at 15:11
![](https://lh3.googleusercontent.com/-XdUIqdMkCWA/AAAAAAAAAAI/AAAAAAAAAAA/4252rscbv5M/photo.jpg?sz=32)
![](https://lh3.googleusercontent.com/-XdUIqdMkCWA/AAAAAAAAAAI/AAAAAAAAAAA/4252rscbv5M/photo.jpg?sz=32)
Dr. Sonnhard Graubner
67.1k32660
67.1k32660
Substituting $tan x=t$ we get $t^3-3t^2-3t+1=0$ which is much more harder to work with.
â user571036
Aug 7 at 15:25
Not at all, it is $t^3-3t^2-3t+1=(t+1)(t^2-4t+1)$
â Dr. Sonnhard Graubner
Aug 7 at 15:30
Then give me the full solution.
â user571036
Aug 7 at 15:35
I would say please, but you will get $tan(x)=-1$ or $tan(x)=2pm sqrt3$
â Dr. Sonnhard Graubner
Aug 7 at 15:38
add a comment |Â
Substituting $tan x=t$ we get $t^3-3t^2-3t+1=0$ which is much more harder to work with.
â user571036
Aug 7 at 15:25
Not at all, it is $t^3-3t^2-3t+1=(t+1)(t^2-4t+1)$
â Dr. Sonnhard Graubner
Aug 7 at 15:30
Then give me the full solution.
â user571036
Aug 7 at 15:35
I would say please, but you will get $tan(x)=-1$ or $tan(x)=2pm sqrt3$
â Dr. Sonnhard Graubner
Aug 7 at 15:38
Substituting $tan x=t$ we get $t^3-3t^2-3t+1=0$ which is much more harder to work with.
â user571036
Aug 7 at 15:25
Substituting $tan x=t$ we get $t^3-3t^2-3t+1=0$ which is much more harder to work with.
â user571036
Aug 7 at 15:25
Not at all, it is $t^3-3t^2-3t+1=(t+1)(t^2-4t+1)$
â Dr. Sonnhard Graubner
Aug 7 at 15:30
Not at all, it is $t^3-3t^2-3t+1=(t+1)(t^2-4t+1)$
â Dr. Sonnhard Graubner
Aug 7 at 15:30
Then give me the full solution.
â user571036
Aug 7 at 15:35
Then give me the full solution.
â user571036
Aug 7 at 15:35
I would say please, but you will get $tan(x)=-1$ or $tan(x)=2pm sqrt3$
â Dr. Sonnhard Graubner
Aug 7 at 15:38
I would say please, but you will get $tan(x)=-1$ or $tan(x)=2pm sqrt3$
â Dr. Sonnhard Graubner
Aug 7 at 15:38
add a comment |Â
up vote
0
down vote
You can divide with $tan x tan 2x-1$ iff $tan x tan 2xne 1$
so $$2tan^2xover 1-tan^2x neq 1implies tan x neq pmsqrt3over 3 $$
so $xneq pm pi over 6+pi cdot k;; k in mathbbZ$.
add a comment |Â
up vote
0
down vote
You can divide with $tan x tan 2x-1$ iff $tan x tan 2xne 1$
so $$2tan^2xover 1-tan^2x neq 1implies tan x neq pmsqrt3over 3 $$
so $xneq pm pi over 6+pi cdot k;; k in mathbbZ$.
add a comment |Â
up vote
0
down vote
up vote
0
down vote
You can divide with $tan x tan 2x-1$ iff $tan x tan 2xne 1$
so $$2tan^2xover 1-tan^2x neq 1implies tan x neq pmsqrt3over 3 $$
so $xneq pm pi over 6+pi cdot k;; k in mathbbZ$.
You can divide with $tan x tan 2x-1$ iff $tan x tan 2xne 1$
so $$2tan^2xover 1-tan^2x neq 1implies tan x neq pmsqrt3over 3 $$
so $xneq pm pi over 6+pi cdot k;; k in mathbbZ$.
edited Aug 7 at 16:09
answered Aug 7 at 15:12
![](https://i.stack.imgur.com/YmkWS.png?s=32&g=1)
![](https://i.stack.imgur.com/YmkWS.png?s=32&g=1)
greedoid
26.7k93574
26.7k93574
add a comment |Â
add a comment |Â
up vote
0
down vote
The particular solutions ($0<x<2 pi$) are $dfrac pi 12$ and $dfrac 5 pi 12$, but when you work out both Wolfram Alpha's and the OP's solution, both general solutions come out to $$dfrac pi (4n+1)12$$
The problem with that is you have to have a restriction for $n=2, n=5, n=8$ and $n=11$, which causes $tan 2x$ to be undefined. To restrict those values, we can write
$$begincases
x = infty, & text$forall n$ a multiple of $3n-1$ \
x = dfrac pi (4n+1)12, & text$forall n$ not a multiple of $3n-1$
endcases$$
The reason why Wolfram Alpha wrote its general solutions as $$x = n pi - dfrac 7 pi12 text and x = n pi - dfrac 11 pi12$$ are because the negative angles are complementary to the positive ones, i.e. $frac pi 12$ and $frac 5 pi 12$ counterclockwise around the unit circle are equivalent to $-frac 7 pi 12$ and $-frac 11 pi 12$ clockwise around the unit circle. They also avoid the the undefined solutions altogether.
add a comment |Â
up vote
0
down vote
The particular solutions ($0<x<2 pi$) are $dfrac pi 12$ and $dfrac 5 pi 12$, but when you work out both Wolfram Alpha's and the OP's solution, both general solutions come out to $$dfrac pi (4n+1)12$$
The problem with that is you have to have a restriction for $n=2, n=5, n=8$ and $n=11$, which causes $tan 2x$ to be undefined. To restrict those values, we can write
$$begincases
x = infty, & text$forall n$ a multiple of $3n-1$ \
x = dfrac pi (4n+1)12, & text$forall n$ not a multiple of $3n-1$
endcases$$
The reason why Wolfram Alpha wrote its general solutions as $$x = n pi - dfrac 7 pi12 text and x = n pi - dfrac 11 pi12$$ are because the negative angles are complementary to the positive ones, i.e. $frac pi 12$ and $frac 5 pi 12$ counterclockwise around the unit circle are equivalent to $-frac 7 pi 12$ and $-frac 11 pi 12$ clockwise around the unit circle. They also avoid the the undefined solutions altogether.
add a comment |Â
up vote
0
down vote
up vote
0
down vote
The particular solutions ($0<x<2 pi$) are $dfrac pi 12$ and $dfrac 5 pi 12$, but when you work out both Wolfram Alpha's and the OP's solution, both general solutions come out to $$dfrac pi (4n+1)12$$
The problem with that is you have to have a restriction for $n=2, n=5, n=8$ and $n=11$, which causes $tan 2x$ to be undefined. To restrict those values, we can write
$$begincases
x = infty, & text$forall n$ a multiple of $3n-1$ \
x = dfrac pi (4n+1)12, & text$forall n$ not a multiple of $3n-1$
endcases$$
The reason why Wolfram Alpha wrote its general solutions as $$x = n pi - dfrac 7 pi12 text and x = n pi - dfrac 11 pi12$$ are because the negative angles are complementary to the positive ones, i.e. $frac pi 12$ and $frac 5 pi 12$ counterclockwise around the unit circle are equivalent to $-frac 7 pi 12$ and $-frac 11 pi 12$ clockwise around the unit circle. They also avoid the the undefined solutions altogether.
The particular solutions ($0<x<2 pi$) are $dfrac pi 12$ and $dfrac 5 pi 12$, but when you work out both Wolfram Alpha's and the OP's solution, both general solutions come out to $$dfrac pi (4n+1)12$$
The problem with that is you have to have a restriction for $n=2, n=5, n=8$ and $n=11$, which causes $tan 2x$ to be undefined. To restrict those values, we can write
$$begincases
x = infty, & text$forall n$ a multiple of $3n-1$ \
x = dfrac pi (4n+1)12, & text$forall n$ not a multiple of $3n-1$
endcases$$
The reason why Wolfram Alpha wrote its general solutions as $$x = n pi - dfrac 7 pi12 text and x = n pi - dfrac 11 pi12$$ are because the negative angles are complementary to the positive ones, i.e. $frac pi 12$ and $frac 5 pi 12$ counterclockwise around the unit circle are equivalent to $-frac 7 pi 12$ and $-frac 11 pi 12$ clockwise around the unit circle. They also avoid the the undefined solutions altogether.
edited Aug 9 at 12:19
answered Aug 8 at 0:04
bjcolby15
8191816
8191816
add a comment |Â
add a comment |Â
Sign up or log in
StackExchange.ready(function ()
StackExchange.helpers.onClickDraftSave('#login-link');
var $window = $(window),
onScroll = function(e)
var $elem = $('.new-login-left'),
docViewTop = $window.scrollTop(),
docViewBottom = docViewTop + $window.height(),
elemTop = $elem.offset().top,
elemBottom = elemTop + $elem.height();
if ((docViewTop elemBottom))
StackExchange.using('gps', function() StackExchange.gps.track('embedded_signup_form.view', location: 'question_page' ); );
$window.unbind('scroll', onScroll);
;
$window.on('scroll', onScroll);
);
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
StackExchange.ready(
function ()
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f2875057%2fsolution-of-trigonometric-equation-avoiding-the-undefined-case%23new-answer', 'question_page');
);
Post as a guest
Sign up or log in
StackExchange.ready(function ()
StackExchange.helpers.onClickDraftSave('#login-link');
var $window = $(window),
onScroll = function(e)
var $elem = $('.new-login-left'),
docViewTop = $window.scrollTop(),
docViewBottom = docViewTop + $window.height(),
elemTop = $elem.offset().top,
elemBottom = elemTop + $elem.height();
if ((docViewTop elemBottom))
StackExchange.using('gps', function() StackExchange.gps.track('embedded_signup_form.view', location: 'question_page' ); );
$window.unbind('scroll', onScroll);
;
$window.on('scroll', onScroll);
);
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Sign up or log in
StackExchange.ready(function ()
StackExchange.helpers.onClickDraftSave('#login-link');
var $window = $(window),
onScroll = function(e)
var $elem = $('.new-login-left'),
docViewTop = $window.scrollTop(),
docViewBottom = docViewTop + $window.height(),
elemTop = $elem.offset().top,
elemBottom = elemTop + $elem.height();
if ((docViewTop elemBottom))
StackExchange.using('gps', function() StackExchange.gps.track('embedded_signup_form.view', location: 'question_page' ); );
$window.unbind('scroll', onScroll);
;
$window.on('scroll', onScroll);
);
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Sign up or log in
StackExchange.ready(function ()
StackExchange.helpers.onClickDraftSave('#login-link');
var $window = $(window),
onScroll = function(e)
var $elem = $('.new-login-left'),
docViewTop = $window.scrollTop(),
docViewBottom = docViewTop + $window.height(),
elemTop = $elem.offset().top,
elemBottom = elemTop + $elem.height();
if ((docViewTop elemBottom))
StackExchange.using('gps', function() StackExchange.gps.track('embedded_signup_form.view', location: 'question_page' ); );
$window.unbind('scroll', onScroll);
;
$window.on('scroll', onScroll);
);
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Sign up using Google
Sign up using Facebook
Sign up using Email and Password